TANTANGAN DAKWAH DI MALUKU PERSPEKTIF KONSTRUKSI SOSIAL PETER L. BERGER - Tutupoho, Rahmat Hidayat (Program Studi Manajemen Dakwah Fakultas Ushuluddin Adab dan Dakwah IAIN Manado, 2025)
Da`wah in Maluku continually faces complex challenges due to the rapid development of technology and the flow of information, particularly social media. While these developments have created a limitless virtual space for preachers to convey positive information, they also carry risks by positioning recipients in a passive position, preventing them from validating the information. They also have the potential to spread exclusive and intolerant ideas that threaten the brotherhood of the Maluku community. Although national and local preachers continue to promote good values ​​to maintain peace, the outbreak of communal conflict continues to disrupt security stability. Therefore, this research aims and has the urgency to explore the challenges of da'wah from a social construction perspective. This research uses a qualitative method with a phenomenological approach through four stages: determining the phenomenon, identifying the research problem, identifying philosophical assumptions, and analyzing the phenomenology. The philosophical assumption is that da'wah is socially constructed, dynamic, and contextual, and that technology changes the way da'wah is received. Social construction theory is used as an analytical tool to examine da'wah objectively (structural thinking) and subjectively (individual creativity). The result, although social media offers significant opportunities, direct and content-based da'wah often focuses solely on material gain and monetization, thus tending to instill rigid understandings and potentially eroding inclusive values ​​such as the pela-gandong bond, which serves as the social capital that cements the brotherhood of the Maluku community. Therefore, a social construction approach is relevant in addressing contemporary da'wah challenges because it emphasizes da'wah based on deeply rooted social structures in Maluku, enabling the public to understand, contextualize, and resist the influence of misleading information and teachings that divide diversity.